Numerical Study on the Effects of Boundary Layer Suction on Flow in the Sectorial Transonic Cascade Under Imitated Near-Stall Condition - Ruixing Liang; Huawei Lu; Zhitao Tian; Hong Wang; Shuang Guo (Applied Sciences)
In the experimental study of a compressor’s cascade under the near-stall condition, the test bench has the disadvantages of high risk and high maintenance cost. This paper explores a method of using the inlet guide vane to imitate near-stall conditions instead of the rotor. The suction groove is set in the sectorial cascade so as to explore the aerodynamic performance of the fluid and the change in the flow field structure. Three different schemes are proposed along the suction surface, and the results indicate that the EW2 scheme, which is located behind the separation starting point and near the vortex core of the separation vortex, has the best performance. The suction groove weakens the downwash caused by the boundary layer on the upper endwall, reducing the radial dimension of the corner and suppressing separation. Suction on the upper endwall also increases the pressure difference in the radial direction of the flow passage, resulting in a slight increase in the suction-side horseshoe vortex (HSV) at the hub. An overall loss reduction of 9.4% is achieved when the suction coefficient is 46%, and the corner separation is most effectively suppressed while ensuring that the HSV at the hub only slightly increases.